1978
DOI: 10.1111/j.1471-0528.1978.tb15605.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypofibrinogenaemia and Recurrent Abortion

Abstract: Summary A 26‐year‐old patient, who had had six consecutive spontaneous early abortions, is presented. The patient had hypofibrinogenaemia. The importance of a normal fibrin network in early pregnancy is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Hahn [9] reported 6 spontaneous abortions, all in the first trimester in a patient with con genital hypofibrinogenaemia and postu lated that the mothers' fibrinogen plays a role in the maintenance of early pregnan cy. In contrast, the mother of our proposi ta had 2 abortions in the second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Hahn [9] reported 6 spontaneous abortions, all in the first trimester in a patient with con genital hypofibrinogenaemia and postu lated that the mothers' fibrinogen plays a role in the maintenance of early pregnan cy. In contrast, the mother of our proposi ta had 2 abortions in the second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that from a clini cal point of view, a large number of the preg nant women suffering from congenital hypo fibrinogenemia and dysfibrinogenemia show severe obstetric complications, especially in the first and second trimesters of pregnancy, such as recurrent abortion [1,2] and placen tal abruptio [3,4], These clinical data sup port the hypothesis that fibrinogen is essen tial to maintain permanent and effective pla cental insertion in the uterine decidua. How ever, the minimum level of this protein which has to be present in plasma in order for the placenta to adhere to the uterus throughout pregnancy is still unclear.…”
Section: Introductionmentioning
confidence: 72%
“…Recurrent abortion [12,13] and recurrent placental abruption [11,14] and postpartum hemorrhage [11,[14][15][16][17][18][19][20] have been reported in cases with congenital hypofibrinogenemia. Goodwin [22] reviewed congenital hypofibrinogenemia in pregnancy in the last 30 years.…”
Section: Resultsmentioning
confidence: 99%